IMPLEMENTASI GOOD GOVERNANCE SEBAGAI UPAYA PENCEGAHAN PENYAKIT BIROKRASI DALAM PELAYANAN PUBLIK (STUDI KASUS KASUS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KANTOR KECAMATAN MEDAN HELVETIA - Pangeran Teguh Anugrah; Abdul Kadir; Pin Pin (Jurnal Darma Agung, 2021)
District is part of the government organization that is closest to dealing directly with the community and spearheading the success of regional development, especially in Medan, where the District will be seen directly in planning and controlling development and services, and a reflection of good governance in Medan. The objectives of this study are as follows: (i) to describe the Good Governance implementation in the District, especially in the District of Medan Helvetia, (ii) to analyze the factors that support and inhibit the implementation in the District, especially in the District of Medan Helvetia.The form of descriptive research using a qualitative approach, this research was conducted in the District of Medan Helvetia. The informants consisted of key informants, namely the Head of District and their apparatus as many as 4 people who were determined purposively and the Main informant namely the community who were taken accidentally as many as 20 people at the time of the study. Primary data comes from interviews and secondary data from literature studies and other written documents. After the data and information needed has been collected, the researcher then sifts through the data and information into the research indicators that have been determined. After the data and information are grouped, the researcher then presents the data and analyzes the data qualitatively.Research Results: The good governance implementation in Medan Helvetia District Office refers to the Decree of the District of Medan Helvetia number 138/19-17/SK-MH/IX/2015 on Standard Operating Procedures (SOP) in Medan Helvetia District Environment. In general, the implementation analysis as follows: (i) Standards and Policy Objectives: public servants have attempted to achieve the public service goals they have set, (ii) Resources: human resources and support resources or facilities, researchers see still shortcomings, (iii) Inter-Organizational Relations: inter-organizational relationships implemented in Medan Helvetia District are good, (iv) Characteristics of the Implementing Agent: the characteristics of the existing implementing agent can already be applied by the implementor of public services in both the public service in Medan Helvetia district, (v) Social, Political, and Economic Conditions: on the variable social, economic and political conditions, the implementors of public services in providing public services do not discriminate between each other, (vi) Implementor Disposition: the attitude given by the implementor of public services is friendly and courteous when providing public services. Supporting factors are cooperation with stakeholders, commitment of the head district (Camat), and the economic potential of the region and opportunities of private CSR, while the Inhibitor Factors are Lack of community participation, lack of human resources apparatus, lack of funds and some damaged road and drainage infrastructure.